Systematic Review of the Cost and Cost-Effectiveness of Rapid Endovascular Therapy for Acute Ischemic Stroke. Issue 9 (September 2017) - Sevick, Laura K.; Ghali, Sarah; Hill, Michael D.; Danthurebandara, Vishva; Lorenzetti, Diane L.; Noseworthy, Tom; Spackman, Eldon; Clement, Fiona
Abstract : Background and Purpose—: Rapid endovascular therapy (EVT) is an emerging treatment option for acute ischemic stroke. Several economic evaluations have been published examining the cost-effectiveness of EVT, and many international bodies are currently making adoption decisions. The objective of this study was to establish the cost-effectiveness of EVT for ischemic stroke patients and to synthesize all the publicly available economic literature. Methods—: A systematic review of the published literature was conducted to identify economic evaluations and cost analyses of EVT for acute ischemic stroke patients. Systematic review best practices were followed, and study quality was assessed. Results—: Four-hundred sixty-three articles were identified from electronic databases. After deduplication, abstract review, and full-text review, 17 studies were included. Seven of the studies were cost analyses, and 10 were cost-effectiveness studies. Generally, the cost analyses reported on the cost of the approach/procedure or the hospitalization costs associated with EVT. All of the cost-effectiveness studies reported a cost per quality-adjusted life year as the primary outcomes. Studies varied in regards to the costs considered, the perspective adopted, and the time horizon used. All the studies reported a cost per quality-adjusted life year of <50 000 as the primary outcome. Conclusions—: There is a robust body of evidence for the cost and cost-effectiveness of EVT. The cost analyses suggested that although EVT was associated with higher costs, it also resulted in improved patient outcomes. From the cost-effectiveness studies, EVT seems to be good value for money when a threshold of 50 000 per quality-adjusted life year gained is adopted.